Dependence of B1− and B1+ field patterns of surface coils on the electrical properties of the sample and the MR operating frequency. Issue 1 (4th February 2016) - Vaidya, Manushka V.; Collins, Christopher M.; Sodickson, Daniel K.; Brown, Ryan; Wiggins, Graham C.; Lattanzi, Riccardo
ABSTRACT: In high field MRI, the spatial distribution of the radiofrequency magnetic ( B 1 ) field is usually affected by the presence of the sample. For hardware design and to aid interpretation of experimental results, it is important both to anticipate and to accurately simulate the behavior of these fields. Fields generated by a radiofrequency surface coil were simulated using dyadic Green's functions, or experimentally measured over a range of frequencies inside an object whose electrical properties were varied to illustrate a variety of transmit ( B 1 + ) and receive ( B 1 − ) field patterns. In this work, we examine how changes in polarization of the field and interference of propagating waves in an object can affect the B 1 spatial distribution. Results are explained conceptually using Maxwell's equations and intuitive illustrations. We demonstrate that the electrical conductivity alters the spatial distribution of distinct polarized components of the field, causing "twisted" transmit and receive field patterns, and asymmetries between | B 1 + | and | B 1 − | . Additionally, interference patterns due to wavelength effects are observed at high field in samples with high relative permittivity and near‐zero conductivity, but are not present in lossy samples due to the attenuation of propagating EM fields. This work provides a conceptual framework for understanding B 1 spatial distributions for surface coils and can provide guidance for RF engineers. © 2016 Wiley Periodicals, Inc. Concepts Magn Reson Part B (Magn Reson Engineering) 46B: 25–40, 2016